Application of lipid-based nanoparticles in cancer immunotherapy - Zhang, Zhongkun; Yao, Siyu; Hu, Yingwen; Zhao, Xiaobin; Lee, Robert J. (Frontiers in Immunology, 2022)
Immunotherapy is revolutionizing the clinical management of patients with different cancer types by sensitizing autologous or allogenic immune cells to the tumor microenvironment which eventually leads to tumor cell lysis without rapidly killing normal cells. Although immunotherapy has been widely demonstrated to be superior to chemotherapies, only a few populations of patients with specific cancer types respond to such treatment due to the failure of systemic immune activation. In addition, severe immune-related adverse events are rapidly observed when patients with very few responses are given higher doses of such therapies. Recent advances of lipid-based nanoparticles (NPs) development have made it possible to deliver not only small molecules but also mRNAs to achieve systemic anticancer immunity through cytotoxic immune cell activation, checkpoint blockade, and chimeric antigen receptor cell therapies, etc. This review summarized recent development and applications of LNPs in anticancer immunotherapy. The diversity of lipid-based NPs would encapsulate payloads with different structures and molecular weights to achieve optimal antitumor immunity through multiple mechanisms of action. The discussion about the components of lipid-based NPs and their immunologic payloads in this review hopefully shed more light on the future direction of anticancer immunotherapy.